Nature's challenge to free will - Berofsky, Bernard (Oxford : Oxford University Press, 2012)
Bernard Berofsky argues that there is room in a deterministic world for a conception of free will as self-determination including the power of genuine choice. He grounds this compatibilist position in a new version of the regularity theory of laws, derived from David Hume's denial of necessary connections in nature.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes bibliographical references and index.
Keywords: Free will and determinism